The Influence of the Madrasah Principal’s Interpersonal Communication on Teachers’ Organizational Citizenship Behavior (OCB) in Madrasah Aliyah - M. Rasyid Ridlo (Indonesian Journal of Education and Science, 2026)
This study analyzes the direct effect of principals’ interpersonal communication on teachers’ organizational citizenship behavior (OCB) in Madrasah Aliyah in Central Lombok, Indonesia. OCB refers to discretionary extra-role behaviors that are not formally rewarded but support school effectiveness. Recent evidence highlights teachers’ OCB as a key determinant of collaboration and student outcomes, while leadership and the way principals exercise power are important antecedents. A quantitative survey with a causal design was employed. The population consisted of 2,665 Madrasah Aliyah teachers, from which 348 were selected through multi- stage simple random sampling. Principals’ power and teachers’ OCB were measured using validated Likert-type scales. Data were analyzed using descriptive statistics and path analysis. The findings show that teachers’ OCB is generally at a moderate level, while principals’ power is perceived as relatively high. Path analysis indicates that principals’ power has a positive and statistically significant direct effect on teachers’ OCB (p31 = 0.118; t = 2.793; p< 0.05). The study concludes that effective and constructive use of power by principals fosters higher OCB among teachers. The results imply the need to strengthen principals’ of openness, empathy,supportivinees, positiveness, and equality to cultivate extra-role behaviors that support the improvement of with teachers. This finding also reinforces leadership development programs as a strategic approach to enhancing school climate, teacher engagement, and overall institutional performance.